Values, attitude, and desire in organic food purchase intention in Mexico - Leyva-Hernández, Sandra Nelly; Toledo-López, Arcelia; Hernández-Lara, Ana Beatriz; Arango-Ramírez, Paola Miriam; Avendaño-Rito, María del Carmen (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis investigation analyses the purchase intention for organic foods through the influence of the consumer’s values, attitude, and desire, how this attitude mediates the relationship between consumer values and purchase intention, and how consumer desire mediates the relationship between attitude and purchase intention.MethodsThe quantitative approach was used with a transversal type of research. Data was collected through a survey of 204 consumers of organic foods in Mexico. The analysis of these results was carried out through partial least squares structural equation modeling.ResultsOnly appearance consciousness and environmental awareness are the motivators of the goals to influence the behavior of consumers when attitude mediates the relationships. However, when attitude mediated the relationship, health consciousness and social awareness were not significant motivators of behavioral intention.DiscussionThis analysis serves as a basis for deepening the study of gastronomic tourism in rural areas such as Mexico since this type of food is sold in tourist places. The model proposed can be used as a theoretical framework for future studies. Marketers can also use the results in marketing strategies as community marketing in economies like Latin American countries.